HIGH DIETARY DAIDZEIN INTAKE LOWERS CHOLESTEROL LEVELS AMONG POST-MENOPAUSAL WOMEN - Herwana, Elly; Pusparini, Pusparini; Graciela, Audria (Universa Medicina, 2020)
BackgroundMenopause is associated with changes in metabolic profile. Although hormone replacement therapy (HRT) has been shown to have beneficial effects on lipid metabolism, its adverse effects have indicated a need for alternative estrogen-based treatments. Several investigations have evaluated the effects of isoflavones on serum lipid levels in postmenopausal women, but the results were ambiguous. The objective of this study was to determine the relationship of dietary daidzein, genistein, and glycitein levels with lipid profile in postmenopausal women.MethodsA cross-sectional study was conducted involving 186 post-menopausal women. A food recall questionnaire was used to measure dietary genistein, daidzein, and glycitein levels. Serum total cholesterol (TC), low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, and triacylglycerol (TAG) were measured using the enzymatic colorimetric method. Simple and multivariate linear regression were used to analyze the data.ResultsGenistein intake was significantly associated with TC (b=145.48, p=0.023) and HDL cholesterol levels (b=48.80, p=0.032). Daidzein intake was significantly associated with TC (b=-204.60, p=0.003), LDL cholesterol (b=-160.81, p=0.014) and HDL cholesterol levels (b=-67.118, p=0.032). Glycitein was not significantly associated with TC (b=232.78;p=0.133), HDL (b=43.59;p=0.428), and LDL (b=235.84;p=0.116). Dietary daidzein had a more lowering effect on TC (Beta=-2.80) and HDL cholesterol (Beta=-2.67) than had genistein on TC (Beta=2.66) and HDL cholesterol (Beta=2.03).ConclusionsHigh dietary daidzein level has a significant lowering effect on TC, LDL cholesterol and HDL cholesterol in post-menopausal women. Our study supports the advice given to the public to increase soy isoflavone intake in post-menopausal women.